Trocar Puncture With a Sump Drain for Crohn's Disease With Intra-Abdominal Abscess: A 10-Year Retrospective Cohort Study - Liu, Juanhan; Gong, Wenbin; Liu, Peizhao; Li, Yangguang; Zheng, Tao; Hong, Zhiwu; Ren, Huajian; Gu, Guosheng; Wang, Gefei; Wu, Xiuwen; Zhao, Yun; Ren, Jianan (Frontiers in Surgery, 2022)
Background Traditional percutaneous catheter drainage (PCD) and surgical intervention could not always achieve satisfactory results for Crohn’s Disease (CD) patients complicated with intra-abdominal abscess. We proposed a trocar puncture with sump drainage for treatment of CD with intra-abdominal abscess and compared it with conventional PCD and surgical intervention. Methods CD patients with intra-abdominal abscess admitted to our hospital from 2011 to 2020 were identified by reviewing electronic medical records retrospectively and divided into the trocar, PCD, and fecal diverting (FD) group according to ways of treating an abscess. Outcomes, risk factors for abscess recurrence, and postoperative complications were compared among the three groups. Results A total of 69 patients were included and divided into trocar (n=18), PCD (n=29), and FD (n=22) group. Four patients in the PCD group were transferred to receive fecal diverting surgery due to initial treatment failure. The incidence of abscess recurrence was significantly higher in the PCD (48%) and FD (50%) group compared to patients using trocar puncture with sump drain (TROCAR group) (16.7%). There were 8 in TROCAR, 22 in PCD, and 20 patients in the FD group who received enterectomy. None of the patients in TROCAR had an ultimate stoma and the incidence of postoperative complications was statistically lower (0%(TROCAR) vs. 31.8%(PCD) vs. 45%(FD), P < 0.05). Way of initial treating on abscess was significantly correlated with abscess recurrence and postoperative complications. Conclusions Trocar puncture with sump drain had a lower incidence of abscess recurrence, abdominal adhesions, post-drainage, and postoperative complications compared to conventional percutaneous catheter drainage or surgical intervention.